Analysing the performance of MSMEs from a marketing perspective - Rahman, Sarli; Fadrul, F; Suyono, S; Momin, Mujtaba M. (Diponegoro International Journal of Business, 2025)
Covid-19 exacerbates various problems previously faced by MSMEs, including a lack of market knowledge. This study aims to determine the relationship between market knowledge, marketing innovation, and marketing performance of MSMEs in the culinary sector in Pekanbaru City. The results of the analysis of 200 MSME actors in the culinary sector in Pekanbaru City using structural equation modeling techniques (SEM-PLS) show that market knowledge influences marketing innovation and marketing performance. Marketing innovation has no direct effect on marketing performance but can mediate the influence of market knowledge on marketing performance.